DDOS ATTACK DETECTION SIMULATION AND HANDLING MECHANISM - Ahmad Sanmorino; Setiadi Yazid (Faculty of Computer Science - Universitas Indonesia, 2013)
In this study we discuss how to handle DDoS attack that coming from the attacker by using detection method and handling mechanism. Detection perform by comparing number of packets and number of flow. Whereas handling mechanism perform by limiting or drop the packets that detected as a DDoS attack. The study begins with simulation on real network, which aims to get the real traffic data. Then, dump traffic data obtained from the simulation used for detection method on our prototype system called DASHM (DDoS Attack Simulation and Handling Mechanism). From the result of experiment that has been conducted, the proposed method successfully detect DDoS attack and handle the incoming packet sent by attacker.